Rancang Bangun Aplikasi Survei Kepuasan Masyarakat di Lingkungan Pemerintah Kabupaten Musi Banyuasin sebagai Penilaian Kinerja dan Kualitas Pelayanan - Abroida; Ahmad Syazili (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
Improving the quality of public services and the performanceof government institutions can be achieved by evaluating the services. One method to do this is by conducting satisfaction surveys for service users, which yield an index reflecting the quality of the services delivered. Traditionally, survey data collection has been conducted by distributing physical questionnaires to service users, followed by manual tabulation of the responses. This conventional approach is closely related to time efficiency and the effectiveness of work processes. Therefore, the utilization of information and communication technology is essential to enhance the efficiency and effectiveness of service satisfaction surveys. In this study, the author developed a web-based application as a platform for conducting satisfaction surveys regarding the services provided. The development of the survey application employed the Software Development Life Cycle (SDLC) methodology using the Iterative Model. As a result, the implementation of this application is expected to facilitate service providers in conducting satisfaction surveys for service users within the Musi Banyuasin Regency Government.